TAKAFUL INSURANCE IN ISLAMIC COUNTRIES: FORMATION AND DEVELOPMENT, IMPLEMENTATION ISSUES IN UZBEKISTAN - Toshnazarova Lola Shukhratulaevna (Galaxy International Interdisciplinary Research Journal, 2022)
The purpose of this article is to highlight the theoretical views of world scientists on takaful insurance, the problems associated with the emergence and further development of this insurance in the world, the specifics of this insurance and the similarities and differences and advantages of mutual insurance and commercial insurance, as well as takaful insurance. It consists of drawing conclusions about the problems associated with the entry into Uzbekistan, the legal framework and the conceptual framework for further development. The author noted the importance of takaful insurance for Uzbekistan, which has a large Muslim population in Central Asia, due to which this form of insurance can quickly become popular in the country, and for this it is necessary to promote and explain it to the general public.